Evaluation and refinement of thresholds for early migration of total knee replacements as an estimator of late aseptic loosening: an updated systematic review of RSA and survival studies - Raymond Puijk; Jiwanjot Singh; Rowan H Puijk; Elise K Laende; José W M Plevier; Peter A Nolte; Bart G C W Pijls (Acta Orthopaedica)
Background and purpose: This study updates 2 parallel systematic reviews and meta-analyses from 2012, which established the 1-year radiostereometric (RSA) migration thresholds for tibial components of total knee replacements (TKR) based on the risk of late revision for aseptic loosening from survival studies. The primary aim of this study was to determine the (mis)categorization rate of the 2012 thresholds using the updated review as a validation dataset. Secondary aims were evaluation of 6-month migration, mean continuous (1- to 2-year) migration, and fixation-specific thresholds for tibial component migration. Methods: One review comprised early migration data, measured by maximum total point motion (MTPM), from RSA studies, while the other focused on revision rates for aseptic loosening of tibial components from survival studies. Studies were matched based on prosthesis, fixation (i.e., cemented and uncemented, and uncemented with screw fixation), and insert (PFI). For the primary aim, newly included study group combinations were compared with the 2012 RSA thresholds to determine the (mis)categorization rate. For the secondary aims, new thresholds were determined based on revision rates for any reason in national registries (5-year < 3%, 10-year < 5%, 15-year < 6.5%). Results: After matching studies on PFI, a total of 157 survival and 82 RSA studies were included, comprising 504 study group combinations, 51 different PFIs, and 186,974 TKRs. We found that the 2012 thresholds were valid, with a misclassification rate of 0.5% at 5 and 0.3% at 10 years. Mean continuous migration could not be used to identify safe or unsafe implants. For cemented TKR, the 6-month mean MTPM was acceptable below 0.30 mm and unacceptable above 1.10 mm. For uncemented TKR, it was acceptable below 1.10 mm and unacceptable above 1.55 mm. Conclusion: The updated data reaffirm the 2012 RSA thresholds, confirming their validity in estimating revision risks for tibial component aseptic loosening. The newly proposed fixation-specific 6-month migration thresholds were found to be reliable for early identification of unsafe TKR designs, while 1- to 2-year mean continuous migration data were found not to be reliable for this purpose. These findings support and refine the migration thresholds to improve the evidence-based introduction of new TKR systems.